The Rebound Effect of the COVID-19 Pandemic on Clinically Significant Prostate Cancer Diagnosis - Antonio Fanelli; Ugo Giovanni Falagario; Marco Finati; Francesco Guzzi; Antonella Ninivaggi; Luca Montrone; Angelo Cormio; Oscar Selvaggio; Pasquale Annese; Gian Maria Busetto; Carlo Bettocchi; Francesca Sanguedolce; et al. (Applied Sciences)
Background and aim: The effect of the COVID-19 pandemic on delayed screening and consequent diagnosis of prostate cancer (PCa) is yet to be defined. This study aimed to evaluate the impact of the COVID-19 pandemic on PCa diagnosis by comparing the number of prostate biopsies performed and observing the PCa detection rate during pre-COVID, COVID and post-COVID periods. Materials and Methods: A prospectively maintained database was queried to identify patients who received prostate biopsy between January 2018 and December 2022. The cohort was stratified into pre-COVID, COVID and post-COVID periods based on Italian government regulations. The primary study outcomes were the number of biopsies performed and the detection rate of clinically significant PCa (csPCa) in each period. Changes in the median number of biopsies were evaluated using the Kruskal–Wallis test, whereas changes in csPCa were evaluated using the chi-square test. The loess function depicted changes in the number of prostate biopsies and the csPCa detection rate across the study period. Results: Overall, 2502 patients were included; their median age was 68 (62–74) years. The median number of biopsies performed in the pre-COVID, COVID and post-COVID period was 46 (43–56), 39 (27–43) and 46 (40–58), respectively (p = 0.02). The most significant decrease in the number of biopsies performed was observed during the peak of the pandemic, from March to May 2020. The detection rate of csPCa in the three periods was 37%, 34% and 39%, respectively (p = 0.01). The loess function demonstrated a rebound effect on the number of biopsies performed and consequent csPCa diagnosed starting from November 2020, while the same effect was not observed for non-cs PCa. Conclusion: The COVID-19 pandemic caused a significant decrease in the number of prostate biopsies performed and csPCa diagnosed. We demonstrated a rebound effect on csPCa diagnosis after the pandemic. Future studies with longer follow-ups are needed to address the effects of the observed grade migration on the burden of PCa treatment and oncological outcomes.